2016
DOI: 10.1039/c6tc02395a
|View full text |Cite
|
Sign up to set email alerts
|

Constructing small molecular AIE luminophores through a 2,2-(2,2-diphenylethene-1,1-diyl)dithiophene core and peripheral triphenylamine with applications in piezofluorochromism, optical waveguides, and explosive detection

Abstract: Constructing small molecular AIE luminophores through heterocycle-based core with applications in piezofluorochromism, optical waveguide, and explosive detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…The α was thus calculated to be 0.00120 dB/μm (Figure d). It is note that α value is relatively high in those of reported materials . The loss coefficient and red‐shift are mainly affected by the reabsorption during the propagation of the light along the crystal .…”
Section: Methodsmentioning
confidence: 78%
See 3 more Smart Citations
“…The α was thus calculated to be 0.00120 dB/μm (Figure d). It is note that α value is relatively high in those of reported materials . The loss coefficient and red‐shift are mainly affected by the reabsorption during the propagation of the light along the crystal .…”
Section: Methodsmentioning
confidence: 78%
“…Unexpectedly, we found that the high quality single crystal exhibited unique fluorescent waveguide [20][21][22] ability (Figure 4a, i-v). On the other hand, crystal with several cracks inside did not show this ability due to lack of anisotropic character in macroscopic scale ( Figure S6).…”
Section: 5-dimethoxybenzene-14-dicarboxaldehyde: An Emissive Organmentioning
confidence: 82%
See 2 more Smart Citations
“…In contrast,t he ground state displays weaker diffraction peaks suggesting ad isturbed molecular arrangement. [28] The sharp and strong peaks can be restored after fuming by dichloromethane, indicating the recovery of the ordered states. Additionally,t he DSC curves of ground powders of TVA, CPVA,a nd DTVA show clear exothermic transitionp eaks at 85 8C, 99 8C, and 243 8C, respectively,w hich can be ascribed to their coldcrystallization process ( Figure S7).…”
mentioning
confidence: 96%